New species and records of Quedius rove beetles (Coleoptera, Staphylinidae, Staphylininae) from Middle Asia - Salnitska, Maria; Solodovnikov, Alexey (European Journal of Taxonomy, 2022)
This paper is devoted to the fauna of Quedius Stephens, 1829 of Middle Asia. It provides descriptions of two species new to science Quedius (Distichalius) gissaricus sp. nov. from Tajikistan and Q. (Raphirus) viator sp. nov. from Kyrgyzstan. Two more species are reported as potentially new to science, but not formally described: Q. (Microsaurus) sp. from the mutilatus group from Tarbagatay Mountains because it is known only from damaged specimens; Q. (Distichalius) sp. aff. gissaricus, known from a single male found sympatrically with Q. (D.) gissaricus sp. nov., remains undescribed because of the possibility of teratology. Earlier records of Q. umbrinus from Middle Asia are considered doubtful or assigned to Q. pseudoumbrinus. Taxonomic notes on the identity of that species as well as Q. cohaesus and Q. fulvicollis in Middle Asia are provided. Among new distribution records summarized for several species, Q. (Velleius) dilatatus, Q. (Microsaurus) tenellus and Q. (Raphirus) jenisseensis are recorded from the territory of Middle Asia for the first time.